2016
DOI: 10.1007/s00231-016-1918-y
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase dusty fluid flow along a cone with variable properties

Abstract: Abstract:In this paper numerical solutions of a two-phase natural convection dusty fluid flow are presented. The two-phase particulate suspension is investigated along a vertical cone by keeping variable viscosity and thermal conductivity of the carrier phase. Comprehensive flow formations of the gas and particle phases are given with the aim to predict the behavior of heat transport across the heated cone. The influence of i) air with particles, water with particles and oil with particles are shown on shear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Singleton [8] was the first to study the boundary layer analysis for dusty fluid and later on several attempts were made to conclude the physical insight of such two-phase flows (see Ref. [9]- [17]) under different physical circumstances. Very recently, numerical solutions for the influence of thermal radiation on natural convection flow of dusty fluid past a vertical wavy frustum of a cone are presented by Siddiqa et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…Singleton [8] was the first to study the boundary layer analysis for dusty fluid and later on several attempts were made to conclude the physical insight of such two-phase flows (see Ref. [9]- [17]) under different physical circumstances. Very recently, numerical solutions for the influence of thermal radiation on natural convection flow of dusty fluid past a vertical wavy frustum of a cone are presented by Siddiqa et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…Patrulescu et al [15] studied mixed convection nanofluid flow over a vertical frustum of a cone and shown that an increase in the mixed convection parameter decreases the heat transfer characteristics. Siddiqa et al [16] discussed two-phase dusty fluid flow over a vertical frustum of a cone and concluded that the rate of heat transfer rate significantly increases by the inclusion of nanoparticles. Amanulla et al [17] examined Casson nanofluid past a truncated cone texture and analyzed that the buoyancy ratio parameter increases the fluid flow.…”
Section: Introductionmentioning
confidence: 99%
“…One of the important aspects of this problem for fluid phase is that it can treated as Newtonian and non-Newtonian fluids which stimulates continuing interest within this area of research. Theoretical works covering on suspension of dust particles in Newtonian fluid with dissimilar circumstances have been reported by several researchers, as documented in [1][2][3][4][5]. A recent study reported by Kumar et al, [6] caters the problem on dusty fluid flow under the effect of mixed convection over a stretching cylinder by taking into account the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%